Preconception leukocyte telomere length and pregnancy outcomes among women with demonstrated fecundity. Issue 12 (3rd September 2021) - Purdue-Smithe, Alexandra C; Kim, Keewan; Andriessen, Victoria C; Pollack, Anna Z; Sjaarda, Lindsey A; Silver, Robert M; Schisterman, Enrique F; Mumford, Sunni L
Abstract: STUDY QUESTION: Is preconception leukocyte telomere length associated with fecundability, pregnancy loss and live birth among women attempting natural conception with a history of 1–2 prior pregnancy losses? SUMMARY ANSWER: Preconception leukocyte telomere length is not associated with fecundability, pregnancy loss or live birth. WHAT IS KNOWN ALREADY: As women increasingly delay childbearing, accessible preconception biomarkers to predict pregnancy outcomes among women seeking natural conception could improve preconception counseling. Findings of small case–control or cross-sectional studies suggest that telomere attrition is associated with adverse pregnancy outcomes among women undergoing fertility treatment, but prospective studies in non-clinical populations are lacking. STUDY DESIGN, SIZE, DURATION: Participants included 1228 women aged 18–40 years with a history of 1–2 prior pregnancy losses who were recruited at four university medical centers (2006–2012). PARTICIPANTS/MATERIALS, SETTING, METHODS: Preconception leukocyte telomere length was measured at baseline using PCR and reported as a ratio (T/S) in relation to population-specific standard reference DNA. Women were followed for up to six cycles while attempting to conceive. Associations of telomere length with fecundability, live birth and pregnancy loss were estimated using discrete Cox proportional hazards models and log-binomial models. MAIN RESULTS AND THE ROLE OF CHANCE: After adjustment for age, BMI, smoking and other factors, preconception telomere length was not associated with fecundability (Q4 vs Q1 FOR = 1.00; 95% CI = 0.79, 1.27), live birth (Q4 vs Q1 RR = 1.00; 95% CI = 0.85, 1.19), or pregnancy loss (Q4 vs Q1 RR = 1.12; 95% CI = 0.78, 1.62). LIMITATIONS, REASONS FOR CAUTION: Telomere length was measured in leukocytes, which is an accessible tissue in women attempting natural conception but may not reflect telomere length in oocytes. Most women were younger than 35 years, limiting our ability to evaluate associations among older women. Participants had a history of 1–2 prior pregnancy losses; therefore, our findings may not be widely generalizable. WIDER IMPLICATIONS OF THE FINDINGS: Despite prior research suggesting that telomere length may be associated with pregnancy outcomes among women seeking fertility treatment, our findings suggest that leukocyte telomere length is not a suitable biomarker of pregnancy establishment or maintenance among women attempting natural conception. STUDY FUNDING/COMPETING INTEREST(S): This research was supported by the Intramural Research Program of the Eunice Kennedy Shriver National Institute of Child Health and Human Development (National Institutes of Health, Bethesda, MD, USA; contract numbers HHSN267200603423, HHSN267200603424 and HHSN267200603426). The authors have no conflicts of interest to disclose. TRIAL REGISTRATION NUMBER: The trial was registered with ClinicalTrials.gov, number NCT00467363.